Dual regulation of transcription factor Nrf2 by Keap1 and by the combined actions of β-TrCP and GSK-3. (3rd August 2015) - Hayes, John D.; Chowdhry, Sudhir; Dinkova-Kostova, Albena T.; Sutherland, Calum
Abstract : Nuclear factor-erythroid 2 p45 (NF-E2 p45)-related factor 2 (Nrf2) is a master regulator of redox homoeostasis that allows cells to adapt to oxidative stress and also promotes cell proliferation. In this review, we describe the molecular mechanisms by which oxidants/electrophilic agents and growth factors increase Nrf2 activity. In the former case, oxidants/electrophiles increase the stability of Nrf2 by antagonizing the ability of Kelch-like ECH-associated protein 1 (Keap1) to target the transcription factor for proteasomal degradation via the cullin-3 (Cul3)–RING ubiquitin ligase CRL Keap1 . In the latter case, we speculate that growth factors increase the stability of Nrf2 by stimulating phosphoinositide 3-kinase (PI3K)−protein kinase B (PKB)/Akt signalling, which in turn results in inhibitory phosphorylation of glycogen synthase kinase-3 (GSK-3) and in doing so prevents the formation of a DSGIS motif-containing phosphodegron in Nrf2 that is recognized by the β-transducin repeat-containing protein (β-TrCP) Cul1-based E3 ubiquitin ligase complex SCF β-TrCP . We present data showing that in the absence of Keap1, the electrophile tert- butyl hydroquinone (tBHQ) can stimulate Nrf2 activity and induce the Nrf2-target gene NAD(P)H:quinone oxidoreductase-1 ( NQO1 ), whilst simultaneously causing inhibitory phosphorylation of GSK-3β at Ser 9 . Together, these observations suggest that tBHQ can suppress the ability of SCF β-TrCP to target Nrf2 for proteasomal degradation by increasing PI3K−PKB/Akt signalling. We also propose a scheme that explains how other protein kinases that inhibit GSK-3 could stimulate induction of Nrf2-target genes by preventing formation of the DSGIS motif-containing phosphodegron in Nrf2.